(untitled) (Archives of Pediatrics of Uruguay, 2020)
Introduction: broncho-obstructive respiratory pathologies are a frequent cause of hospital admissions, and inhalation remains the main choice of treatment. Objectives: learn about the inhalation technique performed by medical students and postgraduate students of pediatrics and by caregivers of hospitalized children and adolescents. Methodology: prospective, descriptive study carried out from June to August 2019. A questionnaire was prepared about the inhalation technique requiring facial mask, and mouthpiece and about the hygiene of the device. Caregivers were asked to describe the procedure performed when administering inhaled drugs. An intervention was performed explaining the correct technique and the caregiver was asked to describe the procedure again. Medical and Pediatrics’ students were assessed as per the international recommendations. Results: out of 80 participants, 3 performed the procedure appropriately. After the intervention, 27 they performed the technique correctly. 3 participants performed the device hygiene correctly before the intervention, and after the intervention, 44 did it properly. 25 health professionals participated, 15 correctly described the procedure on children under 5 years of age and 7 described it correctly on older children. After the information workshop, 24 managed to adequately describe the technique on children under 5 years of age and 15 for older patients. Conclusions: Most caregivers are unaware of correct inhalation therapy techniques. Regular interventions aimed at evaluating and training patients should be implemented. It is essential to train health staff to improve the quality of use of the device.